THE VETERINARIAN IN PANDEMY SARS-CoV-2 (COVID-19): BACKGROUND AND ATTRIBUTIONS (Revista de Ciência Veterinária e Saúde Pública, 2020)
In December 2019, the world watched in disbelief as a viral epidemic, originating in Wuhan, Hubei Province, China, took on frightening proportions. On January 30, 2020, the World Health Organization (WHO) declared the outbreak of the disease caused by the new coronavirus (SARS-CoV-2) to be a public health emergency of international importance, the highest level of alert of the Organization, as provided in the International Health Regulations (IHR, 2016). On March 11, 2020, the epidemic was declared a pandemic by the WHO. Despite the rapid distribution of the new virus, many countries were reluctant or slow to comply strictly with the prophylactic methods suggested by those who had already experienced the whole situation of threat to the health of their populations.